Christian Religious Education in the Era of Artificial Intelligence: Missiological Opportunities in the Formation of Digital Faith for Generation Z - Benyamin Dadi Ratu Mofu; Diana Binkor Jenbise; Martha Maria Wospakrik (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2026)
Advances in Artificial Intelligence (AI) have transformed the way the younger generation learns, interacts, and constructs religious meaning in the digital space. In this context, Christian Religious Education (CRE) faces new challenges, as the formation of Generation Z’s faith no longer takes place solely in the classroom or church, but also within a digital ecosystem mediated by platforms, algorithms, and AI-assisted content. This study aims to analyze the missiological opportunities for PAK in shaping Generation Z’s digital faith in the AI era. The research employs a qualitative approach based on a literature review using a systematic-narrative review model. Data sources include relevant journal articles, conference proceedings, and academic books, particularly publications from the past five years, retrieved through selected academic databases. Data were analyzed using thematic analysis to identify patterns of meaning, conceptual trends, and research gaps. The synthesis results reveal four main themes. First, AI reconfigures the pedagogical ecology of PAK through personalized learning, academic efficiency, and expanded access to religious knowledge. Second, Generation Z’s faith is formed within a hybrid digital space, meaning their faith identity is influenced by virtual communities, digital spiritual content, and algorithmic logic. Third, this situation opens new missiological opportunities for PAK as a space for digital discipleship, spiritual literacy, and theological curation. Fourth, the use of AI in PAK must be grounded in an ethical-theological framework to avoid oversimplifying faith, introducing bias, and fostering dependence on non-human authorities. This article concludes that PAK in the AI era needs to be developed as a theological, critical, relational, and missionary practice of digital faith formation. Theoretically, this study brings together the discourses of AI, digital religion, and missiology; practically, it provides direction for teachers, churches, and Christian curriculum developers in designing faith-based learning that is relevant to Generation Z.